Fiber Geometry in the Corpus Callosum in Schizophrenia: Evidence for Transcallosal Misconnection - Whitford, Thomas J. (2011)
BACKGROUND: Structural abnormalities in the callosal fibers connecting the heteromodal association areas of the prefrontal and temporoparietal cortices bilaterally have been suggested to play a role in the etiology of schizophrenia. AIMS: To investigate for geometric abnormalities in these callosal fibers in schizophrenia patients using a novel Diffusion-Tensor Imaging (DTI) metric of fiber geometry named Shape-Normalized Dispersion (SHD). METHODS: DTIs (3T, 51 gradient directions, 1.7 mm isotropic voxels) were acquired from 26 schizophrenia patients and 23 matched healthy controls. The prefrontal and temporoparietal fibers of the corpus callosum were extracted by means of whole-brain tractography, and their mean SHD calculated. RESULTS: The schizophrenia patients exhibited subnormal levels of SHD in the prefrontal callosal fibers when controlling for between-group differences in Fractional Anisotropy. Reduced SHD could reflect either irregularly turbulent or inhomogeneously distributed fiber trajectories in the corpus callosum. CONCLUSIONS: The results suggest that the transcallosal misconnectivity believed to be associated with schizophrenia could arise from abnormalities in fiber geometry. These abnormalities in fiber geometry could potentially be underpinned by irregularities in the normative processes of neurodevelopment.